Pathological studies on some marine fish parasites in Egypt - Ali, Abdelmoneim A.; Refat, Nahla A.; Mowafy, Rehab E.; Gaheen, Safaa A.; Amer, Omar H.; AbdelMageed, Manar A (Journal of Advanced Veterinary Research, 2024)
Marine fish is an important source of high-quality, yet relatively cheap animal protein in the Egyptianâ€™s diet. Although most parasitic diseases might not cause direct losses of fish, it has deleterious effects on their weight gain and marketability and weaken the fish’s immune system paving the way for more serious secondary infections. In this study, we recorded the most common parasitic infestations in marine fish in Egypt in the period between winter 2019 to summer 2021 and described their associated pathologic effects. Four hundred fish from seven different fish species (Mugil cephalus, Pomadasys incisus, Gilthead sea bream, Pagrus Pagrus, Morone labrax (sea bass), thunnus thynnus and Caranx crysos) were randomly collected from the Mediterranean and the Red Sea. Out of the 400 examined fish, 197 (49.25%) infestations were recorded. The isolated parasites were a crustacean, two cestodes, and a nematode and were morphologically identified as follows: Ceratothoa oestroides, Callitetrarhynchus gracilis, Tetraphyllidean larvae and Hysterothylacium deardorffoverstreetorum). Among the infested fish, the highest prevalence of infestation was recorded by Ceratothoa oestroides (43.65%) followed by Hysterothylacium deardorffoverstreetorum (31.98%) and Callitetrarhynchus gracilis (24.37%), and the lowest prevalence rate was recorded by the Tetraphyllidean larvae (15.74%). The pathologic macroscopic and microscopic lesions associated with each type of infestation are described underscoring the importance of continuous search for and application of possible safe control measures for marine fish parasites to spare the fish industry the detrimental effects of these infestations.Â